‎‎Let $f:[1‎, +‎\infty)\rightarrow\mathbb{R}$ be a function such that ‎$‎\lim_{n\to\infty} (f(n) - f(n+1)) = 0‎$‎‎. ‎Suppose that $\lambda:[1‎, +‎\infty)\rightarrow\mathbb{R}$‎ ‎is an exp-convex function satisfying the functional equation $\lambda(x) = f(x)‎ + \lambda‎(x-1)$ for $x\geq 1$ and initial condition $\lambda(0) = 0$‎. ‎Then ‎$‎\lim_{n\to\infty} (xf(n) + \sum_{k=1}^n f(k) - f(k+x))‎$‎ is‎ ‎convergent for $x\geq 1$ ‎, ‎and $‎\lim_{n\to\infty} (xf(n) + \sum_{k=1}^n f(k) - f(k+x)) = \lambda(x)$‎. Thanks.


closed as unclear what you're asking by Crostul, Yanior Weg, mrtaurho, zz20s, GNUSupporter 8964民主女神 地下教會 May 4 at 14:42

Please clarify your specific problem or add additional details to highlight exactly what you need. As it's currently written, it’s hard to tell exactly what you're asking. See the How to Ask page for help clarifying this question. If this question can be reworded to fit the rules in the help center, please edit the question.